Mothering Molloy, or Beckett and Cutlery. Issue 1 (April 2019) - Kennedy, Seán
Abstract : This essay reads Beckett's relationship to psychoanalysis as a central concern of Molloy, arguing that Molloy's quest for mother traces Beckett's re-evaluation of the British school of object-relations theory of Wilfred Bion and Donald Winnicott. Tracing fine furniture, in Irish literature of the 1920s and 1930s, as an objective correlative of Anglo-Irish distinction, and linking that tradition to a Winnicottian reading of Molloy's impulsive theft of silverware, I argue that Molloy parodies the language of object-relations in order to situate Beckett newly in relation to it. In other words, Beckett intimates that Molloy's unhealthy obsession with mother is mirrored in psychoanalytic theory itself. In this way, writing Molloy allows him to re-evaluate psychoanalysis in its obsession with 'mother' as the founding site of psychic health and wellness.